Unsustainable charcoal production as a contributing factor to woodland fragmentation in southeast Kenya - Eeva Ruuska (Fennia: International Journal of Geography, 2013)
Drawing from a holistic research approach, this paper contributes to the studies of land cover change and sustainable development in Kenya, and to the planning of sustainable future in Dakatcha Woodland, SE Kenya. As an un-protected global hotspot for biodiversity, Dakatcha Woodland has suffered from unsustainable forest resource use. The relation of charcoal production to land cover change and its socio-economic impact are studied in detail. A supervised land cover classification formed using four SPOT satellite images from 2005/06 and 2011 revealed that the woodland is fragmenting and the Important Bird Area (IBA) demarcation should be reconsidered. Through in-situ observation, household questionnaires and semi-structured expert interviews it was found that more than half of the 90 households assessed are involved in charcoal production which is higher figure than peer studies have suggested, and that the charcoal network offers income to many, but bears an negative impact on the environment. It was discovered that, like in Kenya, in Dakatcha Woodland, too, the demand for woodfuels (charcoal and fuelwood) is one of the key drivers of deforestation and land degradation. As such, woodfuel energy is a cross cutting issue, tying together forest resources, livelihoods and sustainable development, and thus demands further research. Forest management of Dakatcha Woodland must be planned in accordance with all stakeholders in a sustainable manner, drawing from agroforestry and participatory forest management systems, and keeping environmental factors in mind for the maintenance of ecosystem services.